The Past as Prologue: The Importance of History to the Military Profession - Murray, Williamson; Sinnreich, Richard Hart (Cambridge University Press, 2006)
In today's military of rapid technological and strategic change, obtaining a complete understanding of the present, let alone the past, is a formidable challenge. Yet the very high rate of change today makes study of the past more important than ever before. The Past as Prologue, first published in 2006, explores the usefulness of the study of history for contemporary military strategists. It illustrates the great importance of military history while simultaneously revealing the challenges of applying the past to the present. Essays from authors of diverse backgrounds - British and American, civilian and military - come together to present an overwhelming argument for the necessity of the study of the past by today's military leaders in spite of these challenges. The essays of Part I examine the relationship between history and the military profession. Those in Part II explore specific historical cases that show the repetitiveness of certain military problems.